Pan Arctic Collaborative for eHealth Research? - Scott, Richard E.; Khoja, Shariq; Durrani, Hammad (Global eHealth Research and Training Program, University of Calgary, Calgary, AB, CA, 2009)
Placed in the context of the relevance of ehealth to the Arctic, and research into ehealth adoption and application, as well as the evidence of sparse publication of ehealth activities in the circumpolar region, an approach focusing on a pan-Arctic collaborative for ehealth research in the north could prove valuable. The report describes development of PANACeA (Pan Asian Collaborative for evidence-based ehealth Adoption and Application) and some of the challenges and successes experienced in applying the research network model. It concludes by speculating on the potential advantages a networked ehealth research approach might have for the northern circumpolar region.